MENINGKATKAN KEMAMPUAN MENGHITUNG SATUAN PANJANG MELALUI MEDIA BAGAN TABEL BAGI ANAK BERKESULITAN BELAJAR MATEMATIKA - Otri Wanarsi (Jurnal Penelitian Pendidikan Khusus, 2014)
ABSTRACT This research was conducted based on the problem found in the fild indicating that a student with mathematics learning disabilities in class IV of SDN 14 Koto Lalang Padang. Got difficulties in calculating the unit of length especially in calculating kilometer to millimeter in multiplication system of one level, two levels, three levels to six level. Based on this problem, this research was aimed at proving that the use of table chart could improve the unit of  length calculating ability of the students with mathematics learning disabilities in class IV SDN 14 Koto Lalang Padang.